Genet's Fantastic Voyage in Miracle de la Rose: All at Sea about Maternity - Elizabeth Richardson Viti (Studies in 20th & 21st Century Literature, 1990)
Together psychoanalytical and feminist criticism appear to uncover the very composition of Jean Genet's inversion. Indeed, in this regard the Miracle de la Rose dream sequence which focuses on an extraordinary voyage through the body of Harcamone, the very imprimatur of bisexuality defined in Cixous' Le rire de la méduse, holds singular importance. Abandoned by his biological mother, Genet sees himself as a "produit synthétique" who has to belong to someone in order to be. Genet simply does not exist unless he can establish, not the Lacanian Name-of-the-Father, but rather the Name-of-the-Mother. The dream reveals a Freudian resolution of ambivalence when its author "kills" the Mother by becoming her through a mediation of Subject and Other which parallels Irigaray's interpenetration of mother and child. Mediation becomes transformation as Genet's fantastic voyage allows him to say, "je nais."
Keywords: psychoanalytical; feminist criticism; feminism; Jean Genet; Miracle de la Rose; dream sequence; voyage; Harcamone; bisexuality; Cixous; Le rire de la méduse; Abandoned; biological mother; mother; Genet; produit synthétique; Lacanian; Name-of-the-Father; Name-of-the-Mother; Freudian; author; kills; mediation; subject; other; parallels; Irigaray; child; je nais; fantastic voyage